Clinical Effectiveness of the Queen Square Intensive Comprehensive Aphasia Service for Patients With Poststroke Aphasia. Issue 10 (10th June 2021) - Leff, Alexander P.; Nightingale, Sarah; Gooding, Beth; Rutter, Jean; Craven, Nicola; Peart, Makena; Dunstan, Alice; Sherman, Amy; Paget, Andrew; Duncan, Morvwen; Davidson, Jonathan; Kumar, Naveen; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Poststroke aphasia has a major impact on peoples' quality of life. Speech and language therapy interventions work, especially in high doses, but these doses are rarely achieved outside of research studies. Intensive Comprehensive Aphasia Programs (ICAPs) are an option to deliver high doses of therapy to people with aphasia over a short period of time. Methods: Forty-six people with aphasia in the chronic stage poststroke completed the ICAP over a 3-week period, attending for 15 days and averaging 6 hours of therapy per day. Outcome measures included the Comprehensive Aphasia Test, an impairment-based test of the 4 main domains of language (speaking, writing, auditory comprehension, and reading) which was measured at 3 time points (baseline, immediately posttreatment at 3 weeks and follow-up at 12-week post-ICAP); and, the Communicative Effectiveness Index, a carer-reported measure of functional communication skills collected at baseline and 12 weeks. Results: A 2-way repeated measures multivariate ANOVA was conducted. We found a significant domain-by-time interaction, F =12.7, P <0.0005, indicating that the ICAP improved people with aphasia's language scores across all 4 domains, with the largest gains in speaking (Cohen's d =1.3). All gains were maintained or significantly improved further at 12-week post-ICAP. Importantly, patients' functional communication, as indexed by changes on the Communicative Effectiveness Index, also significantly improved at 12-week post-ICAP, t =5.4, P <0.0005, also with a large effect size (Cohen's d =0.9). Conclusions: People with aphasia who participated in the Queen Square ICAP made large and clinically meaningful gains on both impairment-based and functional measures of language. Gains were sustained and in some cases improved further over the subsequent 12 weeks.